Q. 4 D4.5( 8 Votes )

# Expand each of the following, using suitable identities  = [ + + 1]2

Using (x + y + z)2 = x2 + y2 + z2 + 2xy + 2yz + 2zx

Here x = , y = and z = 1 = + + 12 + 2 + 2 (1) + 2(1)  = + + 1 + + (-b) +  = + + 1 - – b + Therefore = + + 1 - – b + Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Polynomials - Zero to Hero42 mins  Genius Quiz | Polynomials40 mins  Zeros and Degrees of a Polynomial41 mins  Champ Quiz | Polynomials29 mins  Genius Quiz | Division of Algebraic Expressions37 mins  Introduction to Polynomials37 mins  Quiz | Imp. Qs. on Algebraic Identities65 mins  Basic understanding of Polynomials37 mins  Methods to find zeroes of a Polynomial-246 mins  Remainder Theorem and Factor Theorem38 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 